Altered CD45 expression in C77G carriers influences immune function and outcome of hepatitis C infection. Issue 8 (27th February 2006) - Dawes, R; Hennig, B; Irving, W; Petrova, S; Boxall, S; Ward, V; Wallace, D; Macallan, D C; Thursz, M; Hill, A; Bodmer, W; Beverley, P C L; et al.
Abstract : Background: A polymorphism in exon 4 (C77G) of CD45 that alters CD45 splicing has been associated with autoimmune and infectious diseases in humans. Objective: To investigate the effect of C77G in hepatitis C virus (HCV) infected individuals and study the phenotype and function of peripheral blood mononuclear cells (PBMC) from healthy and hepatitis C infected C77G carriers. Results: C77G individuals showed an increased proportion of primed CD45RA and effector memory CD8 T cells and more rapid activation of the lymphocyte specific protein tyrosine kinase (Lck) following CD3 stimulation. Transgenic mice with CD45 expression mimicking that in human C77G variants had more activated/memory T cells, more rapid proliferative responses, and activation of Lck. Conclusions: Changes in CD45 isoform expression can alter immune function in human C77G variants and CD45 transgenic mice. The C77G allele may influence the outcome of HCV infection.